Analysis of Opportunities and Threats of Social Media in Shaping Students' Character from the Perspective of Islamic Education - Wiratama, Hanif Syairafi; Hafidz, H (Universitas Muhammadiyah Surakarta, 2023)
Social media is a social structure that comes from individuals and organizations bound by their users' similarity. Social media is online media (online media) that is used as a means of online social interaction on the internet. On social media, users can interact with each other, communicate, share networking, and various other activities online. Social media was created to meet human requirements because humans, as social creatures, were created to socialize. Because the development of the times is getting more advanced, the main goal of which is to facilitate users or users of social media so that they can connect with someone in one country, even between countries and between continents, practically and not waste time or provide convenience for users to socialize. However, in the current modern era, social media does not function as usual; it turns out that it influences the character education of students who use it, whether it's a positive or a negative influence, such as showing off on social media or others. Strengthening the formation of student's character through character education in the current context is very relevant to overcoming the moral crisis that is happening in schools and universities. Whether it is admitted or not, there is currently a worrisome crisis involving students in the school environment.